Surgical radioguidance with beta-emitting radionuclides; challenges and possibilities: A position paper by the EANM - Fragoso Costa, Pedro; Shi, Kuangyu; Holm, Soren; Vidal-Sicart, Sergi; Kracmerova, Tereza; Tosi, Giovanni; Grimm, Jan; Visvikis, Dimitris; Knapp, Wolfram H; Gnanasegaran, Gopinath; van Leeuwen, Fijs W B (European journal of nuclear medicine and molecular imaging, 2024)
Radioguidance that makes use of β-emitting radionuclides is gaining in popularity and could have potential to strengthen the range of existing radioguidance techniques. While there is a strong tendency to develop new PET radiotracers, due to favorable imaging characteristics and the success of theranostics research, there are practical challenges that need to be overcome when considering use of β-emitters for surgical radioguidance. In this position paper, the EANM identifies the possibilities and challenges that relate to the successful implementation of β-emitters in surgical guidance, covering aspects related to instrumentation, radiation protection, and modes of implementation.
Keywords: radionuklidy; beta částice; Beta Particles; radiační ochrana; nukleární lékařství; radiofarmaka; Radiation Protection; lidé; chirurgie s pomocí počítače; Nuclear Medicine; Surgery, Computer-Assisted; Humans; Radioisotopes; Radiopharmaceuticals